THE EFFECTS OF FAMILISM ON FAMILY CAREGIVER BURDEN IN VIETNAM: THE MEDIATING ROLE OF SOCIAL SUPPORT - Quynh An Ngo; Thi Mai Phuong Tran (Tạp chí Khoa học Đại học Đà Lạt)
This study examines how familism influences caregiver burden through the mediating role of social support among family caregivers of older adults in Vietnam, where rapid population aging presents significant challenges, with life expectancy at 75 years but healthy life expectancy at only 67.5 years (World Health Organization, 2019). Using a quantitative approach, we employ structural equation modeling to analyze data from 201 family caregivers of adults aged 65 and older in Hanoi, Vietnam. The findings revealed that both dimensions of familism–familial obligation and interconnectedness–negatively correlate with caregiver burden and that this relationship is partially mediated by social support. Specifically, stronger familistic beliefs are associated with increased social support, which in turn reduces caregiver burden. This study makes a novel contribution by being the first to examine the complex dynamics between cultural values, social support, and caregiving outcomes in the context of Vietnam, a developing country. The study addresses the current gap in understanding how internal resources (cultural beliefs) and external resources (social support) collectively influence caregiving outcomes. The findings provide valuable insights for developing culturally sensitive interventions and policies by suggesting ways to strengthen family support systems and leverage the existing cultural emphasis on familism. Practical implications indicate that reducing caregiving burden can positively impact employment status and wages for workers in the labor market (Marinho et al., 2022; Skira, 2015). Future research should consider examining additional cultural determinants and assessing intervention effectiveness for enhancing social support within Vietnam’s rapidly aging society.